2022
DOI: 10.33774/coe-2022-c4tbf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Household transmission of the Delta Covid-19 variant in Queensland, Australia: a case series

Abstract: Household transmission plays a key role in the spread of Covid-19 through populations. In this paper, we collected and analysed retrospective case report data and follow-up interview responses from households with a positive case of the Delta Covid-19 variant in Queensland in 2021. The overall secondary attack rate (SAR) among household contacts was 29.6% and the mean incubation period for secondary cases was 4.3 days. SAR was higher where the index case was male (57.9% vs. 14.3%) or aged ≤12 years (38.7% vs. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Previous studies reported a poor adherence to self-isolation rules and the need for better information about isolation/quarantine protocols from public health officials [ 7 ]. Home health care workers care for played an important role in supporting patients with confirmed and suspected COVID-19 who remain at home [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported a poor adherence to self-isolation rules and the need for better information about isolation/quarantine protocols from public health officials [ 7 ]. Home health care workers care for played an important role in supporting patients with confirmed and suspected COVID-19 who remain at home [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%